Slotted e-shape Antenna Design for Dual Frequency Operation - Abu, Maisarah; A. Rahim, Mohamad Kamal (2009)
A slotted e-shape rectangular patch antenna with dual-frequency operation is introduced. The patch dimension of 34 x 23 mm was fabricated using FR4 substrate having thickness of 1.6 mm and permittivity of 4.8. The measured results show that the designed antenna achieves a VSWR ≤ 2 with bandwidth of 3.02% (2.45-2.525 GHz) at lower frequency and 1.65% (6.125 – 6.025 GHz) at upper frequency. The measured gain of this antenna is 3 dB for both working frequencies.